2005
DOI: 10.1590/s1516-44462005000600005
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression: we know the risks, can it be prevented?

Abstract: Postpartum depression: we know the risks, can it be prevented? Depressão pós-parto: sabemos os riscos, mas podemos preveni-la?A b s t r a c t In the past 20 years, there has been increasing recognition that for some women, pregnancy may be burdened with mood problems, in particular depression, that may impact both mother and child. With identification of risk factors for postpartum depression and a growing knowledge about a biologic vulnerability for mood change following delivery, research has accumulated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 80 publications
0
15
0
10
Order By: Relevance
“…1 Lately, it has been recognized that gestation can be complicated by emotional problems such as depression, thus heavily impacting both mother and fetus. 15 The use of medication during pregnancy requires special attention due to the potential risks to the developing fetus. Pregnant women often need psychiatric treatment in face of emotional disorders caused by stress, anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…1 Lately, it has been recognized that gestation can be complicated by emotional problems such as depression, thus heavily impacting both mother and fetus. 15 The use of medication during pregnancy requires special attention due to the potential risks to the developing fetus. Pregnant women often need psychiatric treatment in face of emotional disorders caused by stress, anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Gotlib et al (42) also examined a group of 360 pregnant women during their pregnancy and after the childbirth and came to this conclusion that large number of childbirth did not have considerable effect on postpartum depression. On the contrary, in a study by Zinga et al, the possibility of occurrence of postpartum depression in nulliparous women was greater than that in pluriparous women which can be related to transition to motherhood stage and low level of self-confidence of nulliparous mothers in meeting the needs of the infant (43). Also in another study which was conducted in Kerman, Ghaffarinejad et al concluded that depression rate was greater among nulliparous mothers (44).…”
Section: Discussionmentioning
confidence: 93%
“…However, it is not adequate to discontinue pharmacological treatment in more severe or recurrent cases. Pharmacological treatment and psychotherapy during pregnancy have also proven to be efficient in preventing postpartum depression (Zinga et al, 2005). An intervention study reported that the participation of women in multi-professional educational groups contributed to decreasing the rate of gestational affective disorders (Falcone et al, 2005).…”
Section: Diagnosis and Treatment Of Gestational Depressionmentioning
confidence: 99%